Research workers V. Lebedeva and I. Gryslova in the literary museum estate Jasnaja Poljana. From: Bro 605/4 fol, nr.64 (1958)
Research workers V. Lebedeva and I. Gryslova in the literary museum estate Jasnaja Poljana. From: Bro 605/4 fol, nr.64.